Osteomodulin Gene Expression Is Associated With Plaque Calcification, Stability, and Fewer Cardiovascular Events in the CPIP Cohort. Issue 3 (9th February 2022) - Gonçalves, Isabel; Oduor, Loureen; Matthes, Frank; Rakem, Narjess; Meryn, Jakob; Skenteris, Nikolaos-Taxiarchis; Aspberg, Anders; Orho-Melander, Marju; Nilsson, Jan; Matic, Ljubica; Edsfeldt, Andreas; Sun, Jiangming; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Stable atherosclerotic plaques are characterized by thick fibrous caps of smooth muscle cells, collagen, and macrocalcifications. Identifying factors of plaque stability is necessary to design drugs to prevent plaque rupture and symptoms. Osteomodulin, originally identified in bones, is expressed by bone synthesizing osteoblasts and involved in mineralization. In the present study, we analyzed osteomodulin expression in human carotid plaques, its link with plaque phenotype, calcification, and future cardiovascular events. Methods: Osteomodulin gene expression (OMD ; n=82) was determined by RNA sequencing and osteomodulin protein levels by immunohistochemistry (n=45) in carotid plaques obtained by endarterectomy from patients with or without cerebrovascular symptoms from the CPIP (Carotid Plaque Imaging Project) cohort, Skåne University Hospital, Sweden. Plaque components were assessed by immunohistochemistry, RNA sequencing, and multiplex analysis. Patients were followed for cardiovascular events or cardiovascular death during a median of 57 or 70 months, respectively, using national registers. Results: OMD levels were increased in plaques from asymptomatic patients compared to symptomatics. High OMD levels were associated with fewer cardiovascular events during follow-up. OMD correlated positively with smooth muscle α-actin ( ACTA2 ; r =0.73, P =10 -13 ) and collagen ( COL1A2 ; r =0.4, P =0.0002), but inversely with CD68 gene expression ( r =−0.67, P =10 -11 ), lipids ( r =−0.37, P =0.001), intraplaque hemorrhage ( r =−0.32, P =0.010), inflammatory cytokine, and matrix metalloproteinase plaque contents. OMD was positively associated with MSX2 (Msh Homeobox 2) ( r =0.32, P =0.003), a marker of preosteoblast differentiation, BMP4 (bone morphogenetic protein) ( r =0.50, P =0.000002) and BMP6 ( r =0.47, P =0.000007), plaque calcification ( r =0.35, P =0.016), and was strongly upregulated in osteogenically stimulated smooth muscle cells, which was further increased upon BMP stimulation. Osteomodulin protein was present in calcified regions. Osteomodulin protein levels were associated with plaque calcification ( r =0.41, P =0.006) and increased in macrocalcified plaques. Conclusions: These data show that osteomodulin mRNA and protein levels are associated with plaque calcification in human atherosclerosis. Furthermore, osteomodulin mRNA, but not protein levels, is associated with plaque stability.